Clinical Predictors of Poorly-Controlled Childhood Epilepsy: A Case-Control Study (Medicine Today, 2020)
Introduction:The aim of the present study was to determine clinical factors associated with poorly controlled epilepsy.Materials and Methods: This retrospective study was performed from January 2007 to December 2008 at Paediatric Neurology outpatient department in Bangabandhu Sheikh Mujib Medical University, Dhaka, among the children with epilepsy of 7 months to 15 years age who had history of at least 6 months treatment with rational antiepileptic drugs daily with adequate compliance. There were two groups of patients; group 1, consisted of 50 poorly controlled epilepsy patients and group 2, comprised 50 well-controlled epilepsy patients. We retrospectively reviewed EEGs and medical records from these children. Features of clinical findings were compared between the two groups.Results: In this study, age of onset of initial seizure before 1 year, mixed type of seizure, infantile spasm, high initial seizure frequency (daily seizure), symptomatic etiology, mental retardation, neonatal seizure and more than 20 seizures before starting treatment were also found to be significant clinical predictors of poorly controlled epilepsy. Multivariate analysis detected 2 independent clinical predictors of poorly controlled epilepsy: mixed seizures and more than 20 seizures before starting treatment.Conclusions: The study showed several clinical factors that can be identified early in the course of childhood epilepsy which can predict development of poor seizure control. Knowledge of these factors will help us to discriminate our patients and pay more attention to those at risk of developing poorly controlled epilepsy.Medicine Today 2020 Vol.32(2): 85-90